Epiphytic communities associated with citrus huanglongbing in areas with and without application of biofertilizer (Research, Society and Development, 2021)
Huanglongbing (HLB) is the most serious disease for citrus. Plants little affected by pathogens can be explained by interactions between microbial populations and plants. The restructuring of communities can be made by the use of biofertilizers, with the potential to suppress disease by stimulating beneficial microorganisms. The objective of this study was to evaluate the epiphytic communities of citrus associated with HLB in areas with and without application of biofertilizers. Leaf samples were collected randomly from symptomatic, asymptomatic and healthy trees. Total fungi, nitrogen fixers and total bacteria were evaluated by counting colony forming units (CFU) on culture medium . The data were analyzed in a 2x3 factorial, submitted to analysis of variance and means were compared by Tukey test (p